OPINI MAHASISWA TERHADAP PERNIKAHAN MELALUI TA’ARUF DILINGKUNGAN UIN SUSKA RIAU - Restia, Rini; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
An individual opinion appear couse of perseption toward of problems insociety.in this research explains how collegian opinions of UIN SUSKA RIAUabout Ta’aruf marriage processly. marriage of Ta’aruf is explain a marriage asperform a religious serrice,applied comprehension of islam and follow theprophet friends beforehand. while for sosial function is extend of religion, asasosial control and declare a certain deed to be islam. the beckground of thisresearch is Ta’aruf marriage processly is used to UIN Suska Riau collegian circleto builded houshold. beside that no guarantee for someone who do relation willuntil marriage. purpose of this research is to know formation collegion opiniostoward Ta’aruf marriage processly in UIN Suska Riau and to know influencefactors of formation collegion opinion of Ta’aruf.Method applied in doing this research is qualitative descriptive.datacollection te techniques used are based on reality in field through observation,interviews,and documentations. informans in this research amounted to 8 people,3 murobbi people as mediator Ta’aruf process and 5 collegion people who havedid marriage of Ta’aruf, based on snowbal method. Data analysis techniqueswere used that model of interactive data analysis. as for checking the validity ofthe data the extension of triangulation.The resuit soed that the elements of the formation of collegian. opinion ofUIN Suska Riau in doing Ta’aruf is feeling that they enter on household with behappy, and then behavior not found awkwardness attitude after married.thecognitionly that comprehension of UIN Suska Riau collegian who have didTa’aruf is a suggestion and don’t worry to walk on it. factors that influence theformation of collegian opinion of Uin Suska Riau toward marriage of ta’aruf is :1. cultural background 2. the past experience,3. values contained is : socialvalues, religion values, cultural values and attitude values.Keyword: Opinion, Marriage, Ta’aruf